Does Incentives Effect on Job SatisfactionEmployees? - Nurhayana, Nurhayana (International Journal of Applied Management and Business, 2023)
This study aims to determine the effect of incentives on employee job satisfaction at PT. Dharma Guna Wibawa Riau Branch. The population in the study amounted to 31 people, because the data was less than 100, the sampling technique was saturated sampling so that the sample was all permanent employees, totaling 31 respondents, the data collection technique was through observation and questionnaires. Data analysis techniques used are validity test, normality test and reliability test, simple linear regression analysis, simple correlation coefficient, T test and r square test. processed using the Statistical Product and Service Solution (SPSS) version 23.0 program. based on the results of the instrument test, all data meet the validity, reliability and normal distribution tests. The results of the study are in accordance with the hypothesis where the t-count value is 2. 678 is greater than t-table (1,699) with a significant level of 0.005 equal to α 5% (0.05), the magnitude of the effect is 45.3%. Based on the research results, the incentive variable has an effect on employee job satisfaction at PT. Dharma Guna Wibawa, Riau Branch.